Simulation-based surgical skill training in internship program - Surekha Rathod; Dhanashree Ghoderao; Vrinda Kolte; Nilima Budhraja (Wolters Kluwer Medknow Publications, 2019)
Background: Objective structured assessment of technical skills (OSATS) are crucial in assessing operative skills. The education of basic surgical skill (BSS) depends on precise assessment of their surgical skill levels and competency level. Hence, this study aimed to determine the effectiveness of BSS module on intern's competency and confidence. Materials and Methods: Fifty-four interns were included in the module. Three faculty members were included in the module. The module has been prepared on: (1) Asepsis - surgical hand scrubbing, gloving, gowning. (2) Simple interrupted suturing. Intervention: Small group teaching was given to each batch, and hands-on training in dry skill laboratory on simulation was given. Interns were assessed by OSATS, and feedbacks were taken at the end of the assessment. Results: The score of global rating scale for each trainee increased within the 15 days of posting. The knowledge domain of posttest score also improved. Conclusion: BSS module was found to be effective, aiding for the interns to improve their knowledge and skills.